Faktor-Faktor yang Mempengaruhi Permintaan dan Penawaran: Tinjauan Literatur (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to examine the factors influencing demand and supply through a literature review of key commodities in Indonesia, including shallots, sugar, local consumer goods, and staple foods. The research employs a descriptive-qualitative literature study by analyzing and synthesizing previous research findings. Data collection was conducted through searches in national journal databases, such as Garuda (Garba Rujukan Digital) and Google Scholar. The results reveal that price remains the dominant factor affecting both demand and supply, while non-price factors are increasingly significant. On the demand side, income, preferences, lifestyle, service quality, promotion, and sustainability standards play a crucial role. On the supply side, production costs, input prices, climate, technology, government policies, credit access, and international trade are key determinants. At the micro level, the number of producers, price elasticity, and producer expectations also shape market dynamics. These findings emphasize the need for an integrated market analysis to provide balanced policy recommendations on price stabilization, consumer protection, productivity enhancement, and sustainability.